A Wireless Multi-Channel Physiological Signal Acquisition System-on-Chip for Wearable Devices - Lee, Sheng-Cheng; Lin, Yu -Shan; Chen, Yu-Jui; Chiueh, Herming (My University, 2016)
A novel wireless ExG sensor tag with a multichannel physiological signals acquisition (PSA) system is presented. The presented system, optimized for power efficiency, contains mixed-signal processor system-on-chip (SoC) and Bluetooth Low Energy (BLE) chip for real time recording and wireless transmission. The versatility of the proposed wireless ExG sensor tag is being demonstrated in several biopotential signals, such as electrocardiogram (ECG), electrooculography (EOG), and electromyogram (EMG). The ExG wireless tag with Tablet can be easily achieve 12 hours with 200mAH battery of continuous recording of ExG signals in healthcare application.
Keywords: Wireless; ExG sensor tag; Portable; SoC; Biopotential signals recording